Training of The Canva For Education Usage in Creating Digital Modules to Improve The Pedagogical Competence of Teachers at SDN 1 Liang, Central Maluku Regency: Pelatihan Pemanfaatan Canva For Education dalam Pembuatan Modul Digital untuk Meningkatkan Kompetensi Pedagogik Guru SDN 1 Liang Kabupaten Maluku Tengah - Safarin Zurimi; Yati Tuasamu; Kasriana; Darwin (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
The use of technology in education is essential, especially in supporting the vision of the Kurikulum Merdeka. However, at SD Negeri 1 Liang, the use of interactive media based on Canva for Education has not been fully optimized. Through this community service program, teachers were trained to design digital modules using the platform. As a result, 100% of the 14 teachers successfully created simple animations after the training. They also worked in groups according to their subjects to produce digital learning modules. These educational products were stored on flash drives and CDs for classroom use. The training received positive feedback from participants, with evaluations showing a satisfaction rate of 92.85%. The teachers agreed that the training enriched their knowledge of creating engaging and enjoyable learning modules. The training used interactive methods, including Kahoot games and icebreakers, which motivated and energized participants. Additionally, supporting facilities like internet connection, laptops, and other devices functioned well, contributing to the success of the training. This training has proven effective in fostering teachers, creativity and motivating them to innovate in their teaching practices.